An evaluation of milk quality in and around Rawalakot Azad Kashmir (African Journal of Dairy Farming and Milk Production, 2013)
The present study was conducted to evaluate the quality of milk from Rawalakot and its surroundings. Milk samples were collected from house hold animal, milkman and restaurant milk in order to assess the hygienic status of raw milk, which was collected from three different parts of the city, Rawalakot Azad Jammu and Kashmir. It was observed that the milk samples which were collected from house hold milk showed better quality compared to the other two sources. For the assessment of adulterants, cloton-boiling (COB), alcohol perception and methyleneblue tests were conducted. In COB test, the result was 29% positive in house hold animal milk, 38% in milkman and 38% in restaurant milk; whereas, in COB test, results of milkman and restaurant milk were similar. The results of alcohol tests showed variation among the three sources of milk: in household animal milk (APT) it was 34%; 44% in milkman and 34% in restaurant milk. Methyleneblue test results show variation among the three sources; the mean values of A+, B+, C+ and D+ for HH were 29, 44, 17, 11 and 14%; 62, 11, 14% were recorded for MM; whereas 14, 33, 33 and 11%, in RM, respectively. The quality of milk was different in all three sources. Milk composition was assessed by specific gravity, fat % and acidity test. The result of Gerber test (fat% age) shows slight variation among the three sources of milk (7.00%, 6.31% and 5.55), respectively. The results of specific gravity were 0.128 g/ml for house hold, 1.027 g/ml for milkman and 0.125 g/ml for restaurant milk, respectively. All three sources showed low specific gravity than standards. The result of acidity test shows slight difference in all three sources of milk. The acidity of milk samples was recorded as 0.18 in house hold milk, 0.21 for milkman milk and 0.19 in restaurant milk. The acidity was higher than the standard values in both milkman and restaurant milk. In organoleptic test, the result was based on sensory evaluation and scoring system. The lowest value was 5.5 and highest value was 7.4. As the results show the HH animal milk was graded as good compared to the other two sources of milk.